Multiple Jobholding, May 1973. Summary - Bureau of Labor Statistics (DOL), Washington, DC.; Bureau of Labor Statistics (DOL), Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
Nearly 4.3 million workers held two jobs or more at the same time in May 1973. Multiple jobholders were 5.1 percent of all employees, about the same as in most years in which surveys were made. Four-fifths of all moonlighters were men. The difference between the multiple jobholding rates of Negro and of white workers was not statistically significant. Men whose primary jobs were as teachers below the college level or as protective service workers had the highest moonlighting rates. Men who were postal workers on their first jobs also had a high multiple jobholding rate. Most male multiple jobholders held a full-time job while working at a second job, but female moonlighters were about equally divided between those who had two part-time jobs and those who had a full-time and a part-time job. (MS)
ERIC Note: Special Labor Force Report.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Employment; Employment Patterns; Labor Force; Labor Supply; Multiple Employment; Racial Differences; Seasonal Employment; Sex Differences; Statistical Data; Tables (Data)